Veterinary-led interventions and owner perceptions of male cat sterilization: Insights from a community-based initiative in Malang, Indonesia - Albiruni Haryo; Handayu Untari (Veterinary World)
Background and Aim: Male cat sterilization is often neglected in feline population control strategies due to cultural beliefs, logistical barriers, and misconceptions, especially in developing urban areas. This study aimed to evaluate the effectiveness of a veterinary-led, community-based intervention in Malang, Indonesia, to promote male cat sterilization, improve owner compliance, and explore sociocultural influences on participation.